Organic Fertilizer and Biopesticide Production from Fruit-Vegetable Waste in Kasang Kota Karang Village - Ichwan, Budiyati; Zulkarnain, Zulkarnain; Adriani, Adriani; Eliyanti, Eliyanti; Irianto, Irianto (LPPM Universitas Jambi, 2023)
Kasang Kota Karang is a village located in Kumpeh Ulu Subdistrict, Muaro Jambi Regency, Jambi Province, where most residents engage in vegetable and fruit farming. However, local farmers face challenges such as suboptimal crop growth and yields, as well as high infestation rates of plant pests and diseases, particularly in red chili cultivation. In response, a community service team from the University of Jambi collaborated with farmers through dialogue and participatory discussions to identify a potential solution: utilizing the abundant fruit and vegetable waste available in the farming area to produce Liquid Organic Fertilizer (LOF) and biopesticides. This program aimed to enhance farmers' knowledge and skills in waste processing technology and to improve their income through the potential commercialization of LOF and biopesticide products. The approach used was Participatory Rural Appraisal (PRA), emphasizing active engagement of the farming partners throughout the implementation process. Evaluation results indicated a significant increase in farmers’ understanding and technical capabilities, with over 90% demonstrating improved proficiency. The farming partners expressed strong enthusiasm and commitment to applying and scaling up the use of LOF and biopesticides in their vegetable farming practices, contributing to better crop yields, increased income, and improved environmental health